A two-part Certosa fibula (variant VIId) from the cult place at Monte di Medea in Friuli - Marić, Ana (Arheološki vestnik, 2016)
In this paper one fibula from the cult place at Monte di Medea near Gorizia/Gorica in Friuli will be presented, which is the sole entirely preserved example from this site. It belongs to variant VIId of the Certosa fibulae, but it has an uncommon two-part construction, which was a motive for this detailed discussion. Previous knowledge about this particular variant of the Certosa fibulae is supplemented with description of the typological differences between the d, e and f variants of type VII – which are often improperly distinguished from one another in published treatises – and with examples of the VIId variant published after the year 1976, in order to update the area of its distribution. Its chronology is also discussed, as well as two-part construction of Certosa fibulae, as new phenomenon.